2021
DOI: 10.1038/s41467-021-23887-2
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric benzylic C(sp3)−H acylation via dual nickel and photoredox catalysis

Abstract: Asymmetric C(sp3)−H functionalization is a persistent challenge in organic synthesis. Here, we report an asymmetric benzylic C−H acylation of alkylarenes employing carboxylic acids as acyl surrogates for the synthesis of α-aryl ketones via nickel and photoredox dual catalysis. This mild yet straightforward protocol transforms a diverse array of feedstock carboxylic acids and simple alkyl benzenes into highly valuable α-aryl ketones with high enantioselectivities. The utility of this method is showcased in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
32
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(34 citation statements)
references
References 67 publications
1
32
0
1
Order By: Relevance
“…On the basis of these mechanistic observations and our recent studies, a plausible mechanism is proposed in Figure . The radical alkenylation is initiated by oxidative addition of a vinyl bromide to Ni(0) catalyst I to furnish Ni­(II) species II .…”
supporting
confidence: 53%
See 4 more Smart Citations
“…On the basis of these mechanistic observations and our recent studies, a plausible mechanism is proposed in Figure . The radical alkenylation is initiated by oxidative addition of a vinyl bromide to Ni(0) catalyst I to furnish Ni­(II) species II .…”
supporting
confidence: 53%
“…Elegant studies from Yoon and Meyer on the counteranion effects of photocatalysts have demonstrated that a more coordinating counteranion can lead to a decrease in lifetime or triplet excited-state energy, which might account for such a tunable stereoselectivity achieved by a judicious choice of counteranions . Two chiral nickel catalysts employed in our recent studies on the C­(sp 3 )–H acylation led to low efficiency for this newly developed alkenylation reaction (entries 9 and 10). , Finally, the control experiments revealed that nickel catalyst, photocatalyst, and light are essential for the alkenylation product formation (entry 11).…”
mentioning
confidence: 90%
See 3 more Smart Citations